2021
DOI: 10.1002/iub.2544
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel key molecular signatures in the pathogenesis of experimental diabetic retinopathy

Abstract: Deep mining of the molecular mechanisms underlying diabetic retinopathy (DR) is critical for the development of novel therapeutic targets. This study aimed to identify key molecular signatures involved in experimental DR on the basis of integrated bioinformatics analysis. Four datasets consisting of 37 retinal samples were downloaded from the National Center of Biotechnology Information Gene Expression Omnibus. After batch-effect adjustment, bioinformatics tools such as Networkanalyst, Enrichr, STRING, and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…With the emergence and popularization of gene chip and RNA-seq technology, the search for new diagnostic markers and therapeutic targets for DR and DME becomes more concise. Some genetic biomarkers related to DR and DME have been reported with the help of these techniques ( 15 17 ). However, the relationship between Th17 cells and their related biomarkers and the molecular mechanism of Th17 cells involved in DR and DME have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…With the emergence and popularization of gene chip and RNA-seq technology, the search for new diagnostic markers and therapeutic targets for DR and DME becomes more concise. Some genetic biomarkers related to DR and DME have been reported with the help of these techniques ( 15 17 ). However, the relationship between Th17 cells and their related biomarkers and the molecular mechanism of Th17 cells involved in DR and DME have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…S8E ). Previous work showed that LGSN may act as a component of the cytoskeleton itself [ 13 ]. Meanwhile, vimentin is also one of the key factors contributing to the actin cytoskeleton reorganization in invasive/metastatic GC cells [ 19 ] and is significantly associated with poor overall survival, first progression, and progression-free survival in GC patients (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…LGSN is a key intermediate filament (IF) terminal-differentiation-associated regulator in the lens [ 12 ]. Programmed cell death is a vital procedure in the lens fiber differentiation [ 9 ], and major efforts to understand LGSN have so far focused on lens [ 12 ] and cataract diseases [ 13 ]. However, other studies into cancer have identified LGSN as a tumor-associated antigen and revealed its essential role in lung carcinoma cell survival [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the popularization of the next generation sequencing technology, the transcriptome research method of ribonucleic acid sequencing (RNA-seq) makes it easier to obtain gene diagnostic markers and therapeutic targets of DR and DME. At present, several studies on biomarkers of DR have been reported, but there are few reports about DME (26,27). However, the related genetic markers of CD8+T cells, especially the direct research evidence obtained from the retina, and the molecular mechanism of CD8+T cells involved in DR and DME are not clear.…”
Section: Introductionmentioning
confidence: 99%